Listening to the mothers of individuals with oral fissures - Vanz, Ana Paula; Ribeiro, Nair Regina Ritter (Revista da Escola de Enfermagem da USP, 2011)
This descriptive study was performed using a qualitative approach. The objective was to listen and report on the etiology of the malformation and learn about the beliefs of relatives regarding the manifestation of oral fissures. Data collection was performed from March to June 2009 using semi-structured interview and analyzed using content analysis. Five categories emerged: mother's reaction, feelings of the mothers and of the family, the behavior of the team, knowledge of the causes, and beliefs. The results permitted to learn about the beliefs regarding the theme and adjust the orientations of the nursing tem and other health professionals to mothers of individuals with oral fissures, helping the relatives throughout all the phases of child development during the therapeutic process.